(untitled) (Bangladesh Journal of Public Administration, 2025)
The study aimed to explore the barriers associated with local governance that impede the effectiveness of digital transformation. The study followed the phenomenological approach of qualitative research to explore deeper insights into the problems. The study selected 16 respondents from four municipalities across four divisions (Dhaka, Mymensingh, Rangpur and Rajshahi), using a purposive sampling technique. The major findings are that local government digital infrastructure is not adequate to provide service digitally. The local government revenues are not sufficient to invest in digital equipment, making all departments of the municipality digital. Frequent server downtimes and limited device availability have hampered the service providers’ ability to provide timely services. Service providers receive short trainings and are not effective; instead, they should receive longer, more practical trainings. The government should intensify awareness campaigns and yard meetings to involve all stakeholders, as the majority of elderly individuals lack familiarity with digital services. The government’s existing policies are insufficient for data privacy, and they require updating to align with digital transformation needs. However, e-participation and citizen engagement are playing pivotal roles for effective digital transformation, helping to reduce time, visitation, and cost, ensuring transparency, and fostering citizen trust in the local governance service delivery process.